Effects of Government Research and Development Support Policies on Local Firms' Innovative Performance - Deokho Cho; Kyunghee Choi (European Regional Science Association (ERSA), 2014)
This study basically focuses on the analysis of the net effect of the government R&D support program on the local firms' technology development and its performance. And then it examines whether and how much R&D raises the effects of local firms' technology development and its performance. It basically tries to investigate the net effect of government's R&D support policies. Especially, it focuses on analyzing the net effects of R&D support policies on the innovative performance of local firms in the Gyeongbuk area where these policies were implemented for the first time in Korea. And more specifically it evaluates the performance of the government R&D support policies, using the propensity score matching in order to control the unobserved heterogeneity. This study finally suggests the R&D support policy alternatives and gives some lessons to the other policies and areas.
Keywords: 330; Innovation; Propensity Score Method; Regional Development; Logit Model